Constitutional referendums a theory and practice of republican deliberation - Tierney, Stephen (Oxford : Oxford University Press, 2012)
The constitutional referendum has become a vital feature of modern constitution-making and reform. This book provides an analysis of the theoretical foundations of constitutional referendums, assessing their democratic credentials and the design decisions that affect the value and legitimacy of the referendum process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Referendum; Constitutional amendments